Segregating YKU80 and TLC1 alleles underlying natural variation in telomere properties in wild yeast. - Gianni Liti; Svasti Haricharan; Francisco A Cubillos; Anna L Tierney; Sarah Sharp; Alison A Bertuch; Leopold Parts; Elizabeth Bailes; Edward J Louis (PLoS Genetics)
In yeast, as in humans, telomere length varies among individuals and is controlled by multiple loci. In a quest to define the extent of variation in telomere length, we screened 112 wild-type Saccharomyces sensu stricto isolates. We found extensive telomere length variation in S. paradoxus isolates. This phenotype correlated with their geographic origin: European strains were observed to have extremely short telomeres (<150 bp), whereas American isolates had telomeres approximately three times as long (>400 bp). Insertions of a URA3 gene near telomeres allowed accurate analysis of individual telomere lengths and telomere position effect (TPE). Crossing the American and European strains resulted in F1 spores with a continuum of telomere lengths consistent with what would be predicted if many quantitative trait loci (QTLs) were involved in length maintenance. Variation in TPE is similarly quantitative but only weakly correlated with telomere length. Genotyping F1 segregants indicated several QTLs associated with telomere length and silencing variation. These QTLs include likely candidate genes but also map to regions where there are no known genes involved in telomeric properties. We detected transgressive segregation for both phenotypes. We validated by reciprocal hemizygosity that YKU80 and TLC1 are telomere-length QTLs in the two S. paradoxus subpopulations. Furthermore, we propose that sequence divergence within the Ku heterodimer generates negative epistasis within one of the allelic combinations (American-YKU70 and European-YKU80) resulting in very short telomeres.